Head-to-head comparative study of [68Ga]FAPI-04 PET/CT and [18F]FDG PET/CT in assessing bone metastasis of various cancers: a systematic review and meta-analysis - He, MingLiu; Tan, Jian (Frontiers in Oncology, 2026)
PurposeThe objective of our systematic review and meta-analysis is to compare the performance of [68Ga]FAPI-04 PET/CT and [18F]FDG PET/CT in diagnosing bone metastasis of various cancer types. This analysis aims to provide an objective assessment of the diagnostic capabilities of these two imaging modalities.MethodsWe conducted a search on Embase, Web of Science, Pubmed for articles published between 2023 and 2025 that meet our criteria. This study focuses on exploring the diagnostic value of [68Ga]FAPI-04 PET/CT and [18F]FDG PET/CT in various cancer bone metastases. we used random-effects analysis to assess the diagnostic capabilities of [68Ga]FAPI-04 PET/CT and [18F]FDG PET/CT in patient-based analysis (PB) with bone metastasis and bone metastatic lesion-based analysis (LB).Heterogeneity of the data was assessed through sensitivity analysis. Furthermore, the included studies underwent quality assessment using the QUADAS-2 tool, which is a bias assessment tool utilized for diagnostic test accuracy studies.ResultsIn the initial search, 235 articles were identified, and finally 10 clinical studies were included by excluding related articles. All included studies were retrospective, involved diverse cancer types, and did not contain overlapping patient cohorts from the same institution. In the patient-based analysis (PB), the detection rate of [68Ga]FAPI-04 PET/CT was determined to be 0.99 (95% CI: 0.90–1.00, I²=36.5%), whereas that of [18F]FDG PET/CT was 0.79 (95% CI: 0.54–0.79, I²=62.4%),Sensitivity analysis revealed potential sources of heterogeneity. In the lesion-based analysis (LB), the detection rate of [68Ga]FAPI-04 PET/CT was determined to be 1.00 (95% CI: 0.98–1.00, I²=91.5%), while [18F]FDG PET/CT showed a detection rate of 0.71 (95% CI: 0.61–0.80, I²=95.3%), with no significant sources of heterogeneity identified.ConclusionBy comparing the available data, [68Ga]FAPI-04 PET/CT appears to show a higher detection rate for bone metastases in various malignancies compared with [18F]FDG PET/CT. However, this finding should be interpreted with caution, as pooled sensitivity, specificity, PPV, NPV, DOR, or HSROC analyses could not be performed due to insufficient available data,